Estrategias didácticas con TIC en la enseñanza-aprendizaje de Lengua y Literatura en octavo grado de la Escuela Miguel Riofrío, Loja 2023 - Solano Solano, Liliana Noemy (2023)
In the digital age of the 21st century, the educational world has been significantly influenced by the rapid advancement of Information and Communication Technologies (ICT). These technological tools have transformed the way the teaching-learning process is approached, opening up a vast panorama of possibilities to enrich and optimize the acquisition of knowledge in various areas of education. In this paper, the objective set was to determine the impact of didactic strategies with ICT on the Language and Literature learning, through a pedagogical proposal for the improvement of the teaching-learning of the said subjects. This research was realised at the Miguel Rifrío Primary School, located in the province and canton of Loja. This research comprised a mixed approach, since it allowed to collect, interpret and analyse data, both quantitative and qualitative in a single approach, facilitating the understanding of the research problem realities more efficiently. The sample selection process was carried out by non-probabilistic sampling for convenience, meaning that units of analysis that were readily available to the investigator were selected. In this paper, the results obtained prove that 67% of students have managed to master the required learning, and the remaining 33% of those evaluated have achieved the required learning; therefore, it is concluded that the application of the educational proposal had a positive effect on the performance of students, especially on those who faced difficulties in learning Language and Literature, given that Information and Communication Technologies (ICT) offer a variety of interactive tools and resources that can make the learning process more dynamic and attractive. Key words: Gaming, innovative education, motivational strategies, active learning.